The role of digital transformation within construction project management in South Africa - Snyman, Pierre (University of the Witwatersrand, Johannesburg, 2023)
In the rapidly evolving landscape of South Africa's construction industry, integrating digital technology has emerged as a pivotal factor influencing project management practices. This study delves into the role of digital transformation within construction project management, framed within the context of technological advancements and shifting industry paradigms. This investigation used a qualitative research methodology to gather data through structured interviews with the South Africa construction sector and international professionals. The sample comprised individuals actively involved in project management, offering insights into the current state of digitalisation and challenges in the planning phase of construction projects. The findings reveal a significant integration of digital tools such as CCS MSP and Primavera P6, highlighting their contribution to enhanced efficiency and effectiveness in project management. The study also uncovers the cultural and age-related challenges in adopting these technologies, alongside the role of regulatory reforms and the DD in their implementation. Advanced collaboration methods, including BIM, Virtual and Augmented Reality (VR/AR), and cloud-based tools, were identified as key to improving stakeholder communication and project success. Conclusively, this research underscores the transformative role of digitalisation in construction project management in South Africa. It advocates for strategic policy interventions and targeted training initiatives to bridge the digital divide, particularly among older professionals, and to harness the full potential of digital tools for improved project outcomes. The study provides valued insights for practitioners and policymakers who want to explore and achieve a deeper understanding of the complexities of modern project management in the construction industry during digital transformation.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Digital transformation; Construction project management; Project planning; PM software; Project efficiency; Digital strategy; UCTD; SDG-8: Decent work and economic growth